Religious Education (RE) as a Context: The Subcultures That Shape Teacher’s Work When Teaching This Subject in Australian Catholic Secondary Schools - Brendan Hyde; Anthony Sylvester Anning (Religions)
Religious Education (RE) can be conceived of as a specific context within which secondary RE teachers from diverse backgrounds teach. This context gives rise to distinctive subject subcultures, characterised by a unique set of beliefs, norms, and practices that are shared by teachers who teach RE. Using micronarratives as a way to initiate further discussion and to distil some key points which can be elaborated upon, we illustrate some salient aspects of RE’s subcultures. These include a subculture of ambiguity, boundary crossings and objects, and a confusion of purpose and terms. Knowledge of these may better assist schools—and Catholic Schools’ Departments—to orient and support these teachers in their classroom practice.